2015
DOI: 10.3141/2486-10
|View full text |Cite
|
Sign up to set email alerts
|

Economic Assessment of Access Management Projects in the Houston, Texas, Region

Abstract: The goal of the access management study of the Houston–Galveston Area Council in Texas, was to examine the effects of recommended improvements before, during, and after project implementation in three areas: operations (traffic flow, intersection delay, and corridor delay), safety (crash frequency, crash rates, and comparisons with state averages), and economic (comparison of taxable sales receipts and control for other economic factors occurring during those times). This paper focuses on an economic assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The economics-based literature indicates that access management projects, including median installations and driveway restrictions, have little to no negative impact on the property value or vitality of adjacent businesses ( 11 , 12 ). Additionally, a previous study of driveway restriction impacts on corner lot developments suggests that when a minor roadway access is present, providing unrestricted access to the major roadway does not reduce the amount of travel time required to enter and exit the development, particularly at higher roadway volumes ( 13 ).…”
Section: Development Of the Methodologymentioning
confidence: 99%
“…The economics-based literature indicates that access management projects, including median installations and driveway restrictions, have little to no negative impact on the property value or vitality of adjacent businesses ( 11 , 12 ). Additionally, a previous study of driveway restriction impacts on corner lot developments suggests that when a minor roadway access is present, providing unrestricted access to the major roadway does not reduce the amount of travel time required to enter and exit the development, particularly at higher roadway volumes ( 13 ).…”
Section: Development Of the Methodologymentioning
confidence: 99%
“…Additionally, arterial highways have been shown to have significantly higher travel speeds as well as better traffic levels-of-service on well-managed corridors ( 10 ). Lastly, when considering the resultant effects on roadside businesses, studies have demonstrated that well-managed roadways have little to no impact on the financial outcome of the businesses as well as the overall customer satisfaction at the establishment ( 11 13 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The next section is the summary of data integration process before obtaining the final data set. The chapter concludes with the summary statistics of all variables that were tested in this study, including the crash data and the roadway characteristics 1997, Riffkin, et al 2015, Benz, et al 2015, Shiri, et al 2018.…”
Section: Thesis Structurementioning
confidence: 99%